Search for scalar neutrino superpartners in e+μ final states in pp̄ collisions at s=1.96TeV - Abazov, V; Abbott, B; Abolins, M; Acharya, B; Adams, M; Adams, T; Aguilo, E; Ahn, S; Ahsan, M; Alexeev, G; Alkhazov, G; Alton, A; et al. (2008)
We report a search for R-parity-violating production and decay of sneutrino particles in the eμ final state with 1.04±0.06fb-1 of data collected with the D0 detector at the Fermilab Tevatron Collider in 2002-2006. Good agreement between the data and the standard model prediction is observed. With no evidence for new physics, we set limits on the R-parity-violating couplings λ311′ and λ312 as a function of the sneutrino mass. © 2008 The American Physical Society.